N-acetylcysteine administration does not improve patient outcome after liver resection - Robinson, Stuart M (Blackwell Publishing Ltd, 2013)
Background Post-operative hepatic dysfunction is a major cause of concern when undertaking a liver resection. The generation of reactive oxygen species (ROS) as a result of hepatic ischaemia/reperfusion (I/R) injury can result in hepatocellular injury. Experimental evidence suggests that N-acetylcysteine may ameliorate ROS-mediated liver injury. Methods A cohort of 44 patients who had undergone a liver resection and receiving peri-operative N-acetylcysteine (NAC) were compared with a further cohort of 44 patients who did not. Liver function tests were compared on post-operative days 1, 3 and 5. Peri-operative outcome data were retrieved from a prospectively maintained database within our unit. ResultsAdministration of NAC was associated with a prolonged prothrombin time on the third post-operative day (18.4 versus 16.4 s; P = 0.002). The incidence of grades B and C liver failure was lower in the NAC group although this difference did not reach statistical significance (6.9% versus 14%; P = 0.287). The overall complication rate was similar between groups (32% versus 25%; P = ns). There were two peri-operative deaths in the NAC group and one in the control group (P = NS). ConclusionIn spite of promising experimental evidence, this study was not able to demonstrate any advantage in the routine administration of peri-operative NAC in patients undergoing a liver resection.